Preoperative Patient Preparation for Enhanced Surgical Outcomes: Multidisciplinary Approach of Nursing, General Surgery, Emergency Medicine, Anesthesia, Radiology, and Healthcare Technicians - Abdu H. Ayoub; Nawaf Muneef M Alshammari; Moteeb Dahawi M Alshammari; Nada Shamrock Alotaibi; Sukaina Mohammed Al Ifraid; Ali Salman Jabr Al Jabr; Khmis Ali Salem Al Balawi; Anwar Sami Bohassan; Yahya A. Adawi; Hassan Ali Hassan Nahari; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: The patient preparation before surgery has a crucial role in determining better surgical results and fewer complications and higher rates of patient recovery. It entails a systematic and inter-professional process, which entails integration of personnel from different discipline such as nursing, general surgeons, emergency physicians, anesthesists, radiologists and health-care technologists. The above manner of working enables a genuine all-round appraisal, coordinated management and enabling the delivery of knowledge-based appropriate patient care prior to the set surgical process. Aim of work: To explore the critical role of multidisciplinary collaboration in preoperative patient preparation, emphasizing the contributions of nursing, general surgery, emergency medicine, anesthesia, radiology, and healthcare technicians. Methods: We conducted a comprehensive search in the MEDLINE database’s electronic literature using the following search terms: Preoperative, Patient Preparation, Surgical Outcomes, Multidisciplinary Approach, Nursing, General Surgery, Emergency Medicine, Anesthesia, Radiology, and Healthcare Technicians. The search was restricted to publications from 2016to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion: Patient preparation for surgery is a complex, but a syndicated process that requires significant and combined efforts of the members of a healthcare team. Each category of the healthcare team, which plays its part in a patient’s care, has its specialization, which When combined, adds great value to the surgery. Some of the preoperative care challenges include: Most of these challenges can however not hinder progress in this area due to innovation in technologies, Multidisciplinary teamwork and collaboration among care givers. To conclude one could say that through adequate preparation for a surgery and distraction towards the strengths that come with a multidisciplinary work setting the healthcare providers are able to deliver safer surgeries as wellas improve the general experience of the patients.